Clinical approach to obesity in primary care - TAZEGÜL, GÖKHAN (My University, 2022)
Obesity is a multifactorial and multisystemic pathogenic condition that causes an increased risk of many diseases. As one of the major causes of preventable deaths, it also heavily features among the leading health problems worldwide. One of the main purposes of primary care is to prevent the development of obesity disease. Lifestyle changes, diet, and exercise programs to be made within the scope of primary care are some of the necessary interventions for an effective struggle. Primary care is a key point considering obesity and the pathological conditions caused by obesity. This review article presents the existing clinical approach to obesity in primary care.

Multifaktöryel ve multisistemik bir patogeneze dayanan, birçok hastalıkta risk artışına sebep olan ve önlenebilir ölümlerin önemli nedenlerinden biri olan obezite tüm dünyadaki sağlık sorunlarının başında yer almaktadır. Birinci basamağın temel amaçlarından biri obezite hastalığının gelişmesini engellemektir. Birinci basamak sağlık hizmetleri kapsamında yapılacak olan yaşam tarzı değişikliği, diyet ve egzersiz programları etkin bir mücadale için gerekli müdahalelerden bazılarıdır. Obezite ve obezitenin neden olduğu patolojik tablolar göz önüne alındığında birinci basamak kilit bir noktayı temsil etmektedir. Bu derleme yazımızda birinci basamak sağlık hizmetlerinde obeziteye klinik yaklaşım konusu literatür eşliğinde sunulacaktır.
Keywords: Obesity; primary care; clinical approach; Obezite; birinci basamak sağlık hizmetleri; klinik yaklaşım